Worst-Case-Expectation Approach to Optimization Under Uncertainty - Shapiro, Alexander; Tekaya, Wajdi; Soares, Murilo Pereira; da Costa, Joari Paulo (Operations Research, 2013)
In this paper we discuss multistage programming with the data process subject to uncertainty. We consider a situation where the data process can be naturally separated into two components: one can be modeled as a random process, with a specified probability distribution, and the other one can be treated from a robust (worst-case) point of view. We formulate this in a time consistent way and derive the corresponding dynamic programming equations. To solve the obtained multistage problem, we develop a variant of the stochastic dual dynamic programming method. We give a general description of the algorithm and present computational studies related to planning of the Brazilian interconnected power system.